Proof-of-concept prototype drill-guide for use in medial patello-femoral ligament (MPFL) reconstruction surgery. (2nd January 2019) - van Duren, B. H.; Lebe, M.; Davies, D. C.; Pandit, H.; Somashekar, N.
ABSTRACT: For surgical reconstruction of the medial patello-femoral ligament (MPFL) a variety of techniques are used for fixation of the graft to the medial border of the patella. The bone bridge or V-shaped tunnel technique utilises two tunnels drilled from the medial aspect of the patella that converge centrally creating a tunnel through which the graft is threaded. This technique has advantages: it avoids hardware (bone anchors) and their associated complications, creates a broad attachment of the ligament approximating normal anatomy and the tunnel does not breach the lateral cortex of the patella reducing the risk of patella fracture. In current practice the bony tunnels are created using freehand techniques. These rely on estimation of the patella centre by the surgeon and is subject to wide variation. Additionally this technique can be inefficient, inaccurate and time consuming. To address these disadvantages a new drill-guide device was developed. A prototype drill-guide was constructed using CAD and 3D printing methods. The device was designed to allow the surgeon to accurately and efficiently drill the required v-shaped bone tunnel. To assess the efficacy of the prototype drill guide, an experiment designed to assess a group of ten surgeons with an average of 4.2 years experience performing the task of creating a v-shaped bone tunnel using a free-hand technique and the drill-guide. To determine the accuracy of the tunnel placement, the angle between drill holes, distance from centre of the patella and the amount of over-drill were measured. Procedure duration was also compared. The results revealed that the prototype drill-guide created a more accurate bone bridge than the traditional free hand method. The root mean square error for the distance from centre was 0.50 mm vs 2.12 mm and the angle between tunnels was 2.6O vs 15.9O for the prototype and traditional methods respectively. There was a mean of 8.9 mm over-drill with the traditional method, which was negated when using the guide. Surgeons using the guide were approximately 25% faster than using the traditional free-hand technique. The prototype drill-guide improved the accuracy, reduced the variability, and reduced procedure duration compared to the traditional free-hand technique.